(0,25x-0,75)+(0,4x-1,6)-1/3=0

Simple and best practice solution for (0,25x-0,75)+(0,4x-1,6)-1/3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (0,25x-0,75)+(0,4x-1,6)-1/3=0 equation:



(0.25x-0.75)+(0.4x-1.6)-1/3=0
We get rid of parentheses
0.25x+0.4x-0.75-1.6-1/3=0
We multiply all the terms by the denominator
(0.25x)*3+(0.4x)*3-1-(0.75)*3-(1.6)*3=0
We add all the numbers together, and all the variables
(+0.25x)*3+(+0.4x)*3-1-(0.75)*3-(1.6)*3=0
We add all the numbers together, and all the variables
(+0.25x)*3+(+0.4x)*3-8.05=0
We multiply parentheses
0x+0x-8.05=0
We add all the numbers together, and all the variables
2x-8.05=0
We move all terms containing x to the left, all other terms to the right
2x=8.05
x=8.05/2
x=4+0.050000000000001/2

See similar equations:

| 3x/2=x+5 | | (2x+5)x=348 | | X^2-72=-6x | | 1-3(-8m-7)=7m-8 | | 16=4/5v | | 2y-8.3=3y | | 2x^2+13x-44=0 | | 5x+3=10+12x | | (x-4)(x+1)-(x+7)(x+3)=-7x+17 | | 14x+9+11x-13=146 | | I0n-12-4n+10=70 | | 8/9x+10=90 | | -38-8x=38-12x | | 16−2t=t+9+4tt=t= | | .5(7x-3)=19 | | F=(6x^-2)/(3x^2) | | x-9+1=12 | | 6d+2d-6d+4d=18 | | 22k-13+3k=62 | | 35+9n-28=70 | | .5(x-3+2x-4)=10 | | 6d+2d−6d+4d=18 | | .5(10+2x)=25 | | 12+5w-3=49 | | 2.5/x=9.4 | | .5(6+26x)=3x+43 | | 39÷n=3 | | 2y+9=57 | | 9x+35=4x+60 | | 4s+s-3s-2s+s=2 | | 12+14q-9q=47 | | d^2-40d=0 |

Equations solver categories